Metastatic small bowel occlusion as initial presentation of squamous cell carcinoma of the lung - Costa, Rita Seara; Vieira, Ana Luísa; Costa, Juliana M.; Fernandes, Beatriz; Ferreira, Aníbal (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Costa RS, Vieira AL, Costa J, Fernandes B, Ferreira A. Metastatic small bowel occlusion as initial presentation of squamous cell carcinoma of the lung. Turk J Gastroenterol 2019; 30(5): 492-4.